Internet Addiction as Predictor in Marital Relationship among a Sample of Divorced Women - Harahsheh, Ahmad Hasan Muhareb (Islamic Guidance and Counseling Journal, 2025)
This study investigates the predictive relationship between Internet addiction and marital incompatibility among a sample of divorced women. Given the rapid technological advancements and the pervasive influence of the Internet on marital compatibility, this research examines the extent to which Internet addiction serves as a predictor for marital enhancers and inhibitors of compatibility. Utilizing a sample of 123 divorced women, the study employs the Internet Addiction Scale (IAS) (Cronbach’s alpha= .86) and the Marital Compatibility Inhibitors and Enhancers Scale (MCIES) (Cronbach’s alpha= .76, .72, respectively). The findings reveal a high prevalence of Internet addiction (M=4.23, SD=.57), elevated levels of inhibitors (M=4.18, SD=.64) affecting marital adjustment, and a diminished presence of enhancers (M=1.75, SD=.60) promoting marital compatibility. Statistical analysis demonstrates significant and robust correlations between Internet addiction and both marital adjustment inhibitors (r = .789) and enhancers (r = -.991) among divorced women. Furthermore, Internet addiction accounts for 61.9% of the variance in inhibitors and negatively correlates with 98.2% of the variance in enhancers. The study concluded that the Internet addiction affects the marital relationship, and thus negatively affecting the cohesion of the family and society.